Niveles de ventas en la empresa de logística y Electricidad Caflosa de la ciudad de Babahoyo, periodo 2022. - Paladines Moreira, Iraida Desiree (2023)
The investigation was carried out in the private company called Caflosa, which has been formally operating for 12 years and is engaged in various activities, such as the rental of cranes and other construction equipment, the wholesale of electrical equipment and the rental of commercial real estate. The company is located in the province of Los Ríos, in Babahoyo, Parroquia Clemente Baquerizo. The research focused on studying Caflosa's sales levels in its competitive environment. The company was found to have an acceptable sales revenue stream due to its competitive advantage in terms of its crane fleet. However, a negative aspect is that the company does not advertise in the media or social networks due to security problems. The methodology used was descriptive, using interviews and structured questionnaires. The research is framed in the field of financial, administrative, tax, audit and control management, with a focus on marketing and commercialization. This research is related to the project of management of administrative management processes in the public and private sectors.